Incidence of Insects Attacking Okra and The Avoidable Losses Caused by Them - Chaudhari, H R; Dadheech, L N (Annals of Arid Zone, 2016)
At Udaipur, the summer crop of okra was attacked by Aphis gossypii Glov. (2.89/leaf), Amrasca bigllttllla biguttula Ish. (4.78/leaf). Bemisia tabaci Guen. (0.78/leaf) and Earias fabia St. (57.14% infested fruits). If the crop was not grown under insecticidal protection, the net available loss worked out to be 54.04%.